eHealth Literacy and Adherence to MMS Tablet Consumption Among Millennial and Gen Z Pregnant Women - Nur Putri Erdianti; Erni Rihyanti; Rochmawati (STIKes Budi Luhur Cimahi, 2026)
Adherence to pregnancy supplementation in Indonesia remains low, and eHealth literacy is hypothesized to be associated with supplementation behavior among digitally native pregnant women. This study aimed to analyze the relationship between eHealth literacy and adherence to Multiple Micronutrient Supplement (MMS) tablet consumption among millennial and Gen Z pregnant women. This analytical cross-sectional study was conducted on 108 pregnant women aged 17–40 years in Depok City, Indonesia, who were smartphone users and had received MMS at public health centers (Puskesmas), selected through purposive sampling. eHealth literacy was measured using the eHealth Literacy Scale (eHEALS), and MMS tablet adherence was measured using the Simplified Medication Adherence Questionnaire (SMAQ). Data were collected through Google Forms and analyzed using the Chi-square test (α = 0.05) and Spearman rank correlation. A total of 62.0% of respondents had high eHealth literacy (mean eHEALS score: 28.21 ± 5.34), and 76.9% were adherent to MMS tablet consumption. There was a significant positive association between eHealth literacy and MMS tablet adherence (r = 0.549; p = 0.010), with pregnant women who had high eHealth literacy being 2.72 times more likely to be adherent (crude OR = 2.72; 95% CI: 1.28–5.78). These findings indicate an association rather than a causal relationship. Integrating structured digital-based education to strengthen digital health competence, particularly the ability to appraise online information, into antenatal care services may support adherence to the MMS program.